Investigating the Structural Composition of Contemporary Sustainable Organic Agriculture Supply Chains: A Case Study from Thailand - Rattanawong, Ananya; Ongkunaruk, Pornthipa; Leingpibul, Thaweephan (Duke) (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
The global demand for organic produce has surged, with notable growth among Thai consumers. However, within Thailand's organic agricultural sectors, supply chain obscurity has impeded the understanding and resolution of emerging challenges associated with meeting this rising demand. Public interest has traditionally centered on mainstream economic sectors, resulting in inadequate attention to the sustainable organic farming supply chains. This study aims to explore the complexities of current sustainable organic supply chain configurations in Thailand, addressing gaps that lead to suboptimal planning and non-sustainable practices. Utilizing the Integration Definition for Function Modeling (IDEF0) framework, this research collected data from key stakeholders through in-depth interviews. Participants included representatives from each stage of the supply chain, providing comprehensive insights into the operational dynamics. The analysis identified several critical challenges within the supply chain, including insufficient collaborative planning, reduced productivity, inaccurate demand forecasting, ineffective budgetary planning, and inadequate cold chain management. These challenges highlight the fragmented nature of the current supply chain and the need for strategic improvements. To address these shortcomings, the study suggests integrating technological advancements in demand planning, operations, and budgeting, fostering collaboration among supply chain members, and forming strategic partnerships with cold chain management service providers. These recommendations aim to enhance the efficiency and sustainability of Thailand's organic produce supply chain, ensuring it can meet increasing global and domestic demands effectively.